Прямі іноземні інвестиції: світові тенденції та структурний розподіл в економіці України - Ромусік, Я.В. (Економіка промисловості, 2012)
Досліджено проблему розподілу глобальних потоків прямих іноземних інвестицій у розрізі різних регіонів світу, а також країн із різним рівнем розвитку: розвинутих, з економікою, що розвивається, чи перехідною; визначено ключові особливості інвестиційної політики країн в умовах рецесійних явищ економік світу; виконано аналіз структурного співвідношення вхідних потоків прямих іноземних інвестицій в економіку України.
Ключові слова: іноземні інвестиції, перехідна економіка, інвестиційна політика, економіка України. Исследована проблема распределения глобальних потоков прямых иностранных инвестиций в разрезе различных регионов мира, а также стран с разным уровнем развития: развитых, с развивающейся или переходной экономикой; определены ключевые особенности инвестиционной политики стран в условиях рецессионных явлений экономик мира; проведен анализ структурного соотношения входных потоков прямых иностранных инвестиций в экономику Украины.
Ключевые слова: иностранные инвестиции, переходная экономика, инвестиционная политика, экономика Украины. In the conditions of modern economy enterprises run into high changeability of environment, in particular, with a necessity in good time to adapt the tax plans. Enormous volumes of information that must be analyzed in the process of the tax planning require the presence of the modern informative providing that allows both facilitating the drafting of tax plans and carrying out their correction. It stipulates actuality of researches in the field of development of the informative providing of the operative tax planning at enterprises. The aim of the article is the development of chart of the informative providing of the operative tax planning at an enterprise. In the article the informative providing of the operative tax planning is offered at an enterprise. The informative providing is the complex of associate instruments that provide the stages of the operative tax planning. It allows promoting efficiency of functioning of the Ukrainian enterprises. The development of the offered informative providing can be in terms of methods and mechanisms of its practical realization.
Keywords: informative providing, tax planning, operative planning, taxes of enterprises.